Conducting polymer electrodes for gel electrophoresis. - Katarina Bengtsson; Sara Nilsson; Nathaniel D Robinson (PLoS ONE)
In nearly all cases, electrophoresis in gels is driven via the electrolysis of water at the electrodes, where the process consumes water and produces electrochemical by-products. We have previously demonstrated that π-conjugated polymers such as poly(3,4-ethylenedioxythiophene) (PEDOT) can be placed between traditional metal electrodes and an electrolyte to mitigate electrolysis in liquid (capillary electroosmosis/electrophoresis) systems. In this report, we extend our previous result to gel electrophoresis, and show that electrodes containing PEDOT can be used with a commercial polyacrylamide gel electrophoresis system with minimal impact to the resulting gel image or the ionic transport measured during a separation.